Economic model predictive control of distillation column - Faisal, A. (American Scientific Publishers, 2016)
Although real time optimization (RTO) and model predictive control (MPC) layers are widely applied to optimize the economics of process operations successfully, it only results in a sub-optimal economic performance. Integration of the two layers into a single layer has been shown to offer potential advantages in realizing optimal economic performances. Economic model predictive control (EMPC) has recently been proposed in the literature to enhance the economic performance of process operations. This paper presents some of the basic formulations of economic model predictive control EMPC. The efficacy of EMPC is demonstrated via its application on a pilot-scale distillation column through simulation. Simulation results have shown that different formulations of EMPC outperform the economic performance of RTO and MPC in two layers while maintaining the system stability. Â© 2016 American Scientific Publishers. All rights reserved.